Study of the influence of commitment in social marketing: the case of “Coordinadora de lucha contra la droga, barrio vivo” - Foncubierta Rodríguez, María José (Editorial Universidad Don Bosco, 2017)
In this paper a theoretical model of sustainable behavior is developed. Through this theoretical model, that we have called Commitment Model Applied to Social Marketing, we propose to establish a relation between the use of social marketing strategies from an integrative perspective and the consumer engagement or commitment. The methodology used has been a literature review about some of the most important social marketing and engagement theories. To explain how to apply the model we have used the case method, through the study of the non profit organization: “Coordinadora de Lucha contra la Droga, Barrio Vivo” (“Coordinator for Combating Drugs, Living Neighborhood”), in Algeciras, a city in the of South-East of the province of Cádiz, in the area denominated Campo de Gibraltar. This area has experienced a dramatic amount of drug consumption by a significant part of its youth population, facilitated by its geographical proximity to North Africa.